Hands are not for hitting - Agassi, Martine, 1966-; Heinlen, Marieka (Minneapolis, MN : Free Spirit, 2000)
Demonstrates that "hands are not for hitting" by suggesting many positive uses for them, such as saying hello, playing, creating, and helping.
Includes bibliographical references (p. 35).
School Library Journal.
2.6.
K-3.
Center for the Collaborative Classroom Curriculum.
AD510L
Keywords: School violence -- Prevention -- Juvenile literature; Anger -- Juvenile literature; Hand -- Juvenile literature; Early childhood education -- Activity programs -- Juvenile literature; Behavior; Anger; Violence; Human behavior; Violence; Hand; Behavior; Anger; Violence